A multi-variant approach to optimize process parameters for oil extraction from non edible feedstock: Acacia nilotica. (2020) - Rajeshwaran, M.; Parthasarathi, R.; Ganeshkumar, J.; Ponshanmugakumar, A.
Abstract: The present work aims to optimize the parameters that affect the oil yield using solvent extraction technique. Acacia nilotica (non-edible feedstock) has been suggested as the "Miracle plant" is one of the important tree species found in the arid and semi arid zones of the world. The technique employed to extract oil from Acacia nilotica was Soxhlet extraction. Acacia nilotica due to its non-edible nature, can be converted to biodiesel there by it helps in solving the debate between food and fuel. The extraction were performed using n-Hexane as the solvent at 3:1, 5:1 and 7:1 (v/w) solid to solvent ratios and at three different extraction time periods of 4, 5 and 6 (hrs). The reaction temperature ranges between 60 °C and 70 °C. The optimization was done with the help of Response surface methodology (RSM) generated from the software Design Expert version 7.1.5 using the D-optimal design. The parameters analysed are solvent to seed ratio, reaction temperature and extraction time.